Hotspot Distribution Analysis as Forest and Land Fire Indicators in the New National Capital City (IKN) - Rosalina Kumalawati; Astinana Yuliarti; Jany Tri Raharjo; Rijanta Rijanta; Ari Susanti; Erlis Saputra; Puput Wahyu Budiman; Rahmat Aris Pratomo; Karnanto Hendra Murliawan; Wisnu Putra Danarto; Ghinia Anastasia Muhtar; Rizki Nurita Anggraini (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2023)
East Kalimantan Province is planned as the new national capital city (IKN). Forest and land fires occur regularly every year and their frequency is increasing, especially during the dry season. This research uses secondary data, namely hotspot data. Hotspot data was obtained from the results of the 2012-2022 S-NPP VIIRS image recording. Data analysis in this study used descriptive and statistical analysis. The results of processing and analysis of the distribution of hotspots are overlaid with administrative maps so that the distribution of hotspots in each district in the study area can be identified. The results of the study show that hotspots distribution from the 2012-2022 S-NPP VIIRS image recording in East Kalimantan Province is varies quite a bit in each district. The highest hotspots distribution is in Kutai Kartanegara Regency and the lowest is in Mahakam Ulu and Penajam Paser Utara Regency. The higher number of hotspots is the higher incidence for forest and land fires. The distribution of hotspots needs to be known because it can be a form of early detection and fire mitigation so that the negative impact of fires can be minimized.